Multidisciplinary Firms and the Treatment of Chronic Pain: A Case Study of Low Back Pain - Pilitsis, Julie G.; Khazen, Olga; Wenzel, Nikolai G. (Frontiers in Pain Research, 2021)
Sixteen million people suffer with chronic low back pain and related healthcare expenditures can be as high as $USD 635 billion. Current pain treatments help a significant number of acute pain patients, allowing them to obtain various treatments and then “exit the market for pain services” quickly. However, chronic patients remain in pain and need multiple, varying treatments over time. Often, a single pain provider does not oversee their care. Here, we analyze the current pain market and suggest ways to establish a new treatment paradigm. We posit that more cost effective treatment and better pain relief can be achieved with multi-disciplinary care with a provider team overseeing care.